Psychological Analysis of the Behavior of a Literary Hero - Hassoon, Mohammed Kadhim (Al-Adab Journal, 2022)
The article analyzes the image of male characters in the work of Saltykova- Shchedrina «Provincial essays, which included such essays as «Deceived second lieutenant», «Porfiry Petrovich», «Princess Anna Lvovna», «Pleasant family». The article presents the images of the literary heroes of Ivan Petrovich, Dmitry Borisovich Zhelvakov, Porfiry Petrovich, Tekhotsky and others».The psychological impulses they go through determine their relationships with other literary characters in the context of psychological influence, which reflects Saltykov's tendency to choose such characters. The fate and biography of Saltykov Shedrin's literary characters are closely related to the conditions and circumstances of the society around them. In one way or another, they are a reflection of him, expressing his orientations and aspirations in the various stages of social development that he has gone through. This paper presents Shedrin's view of community relations in a multi-layered environment and the role of each literary character in it, especially since these characters uniquely expressed the popular mood that prevailed in the nineteenth century in Tsarist Russia and during the issuance of some decisions that led to a major change in The Russian society at that time, including the rights of peasants, the endeavors, that aimed justice, equality, liberation of serfs, and other cultural and political movements, that drew the features of Russian society and established a new cultural, social, political and economic stage, that had a great impact on determining the future of Russia later.